Telaprevir in a Patient with Chronic Hepatitis C and Cryoglobulinemic Glomerulonephritis. Issue 5 (July 2014) - De Nicola, Stella; Aghemo, Alessio; Campise, Maria Rosaria; D'Ambrosio, Roberta; Rumi, Maria Grazia; Messa, Piergiorgio; Colombo, Massimo
Mixed cryoglobulinemia (MC), the most common extra-hepatic manifestation of HCV, may lead to renal involvement ranging from mild urinary abnormalities to nephritic syndrome, eventually evolving to renal failure requiring renal replacement therapy. HCV eradication with pegylated interferon (PEG-IFN) and ribavirin (RBV) is the only curative treatment for MC-related membranoproliferative glomerulonephritis. The addition of directly acting antivirals (DAAs) to PEG-IFN and RBV has significantly improved sustained virological response rates in HCV genotype 1 patients. Safety and efficacy of this regimen in patients with membranoproliferative glomerulonephritis has not been proved yet. Here, we report the case of a woman with HCV-1-related cryoglobulinemic membranoproliferative glomerulonephritis presenting with severe nephritic syndrome and rapidly progressive renal failure, who received successful treatment with the DAA telaprevir in conjunction with PEG-IFN and RBV. Triple therapy was safe and effective, leading to HCV eradication and complete resolution of acute renal failure.